Function model for calculating the Water Quality Index - WQI (2023)
Research article "Social and institutional economic variables of greatest influence on the secondgeneration indicators related to the water resource and its management", which was financed by CONADI in 2015. This work shows how functions implemented in PHP and MySql for determining the Water Quality Index (WQI) established by the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM) (2011). It starts by the data and measurements collection at different locations in the Bogotá river basin. © 2019.